STUDI TENTANG NAMA, BENTUK, PENEMPATAN DAN MAKNA MOTIF PADA PAKAIAN RAJA KERAJAAN SIAK SRI INDRAPURA PROVINSI RIAU - DESI PURNASARI, Drs. Yusron Wkarya,M.Pd, Dra. Zubaidah, M.Sn (Universitas Negeri Padang, 2015)
The costumes worn by the king of Siak Sri Indrapura is the manifestationof culture and tradition of Melayu-Riau people. The typical characteristic of the costumes were seen from the movie made of gold thread which was weaved by Siak people. This research was intended to describe the names, forms, placing and motive meanings of costumes of the king of Siak Sri Indrapura in Province Riau. This research applied qualitative method and descriptive approach. The data collected was in the form of primary and secondary data. The primary data was gotten from the visual data of costumes of the king of Siak Sri Indrapura, while the secondary one was gotten from the information given by traditional figures, public figures and library study. The data was gathered through observation, interview and documentation.Kata Kunci: Nama, Bentuk, Penempatan, Makna Motif, Pakaian Raja Kerajaan Siak Sri Indrapura Provinsi Riau